KAMPUNG KOTA SEBAGAI SEBUAH TITIK TOLAK DALAM MEMBENTUK URBANITAS DAN RUANG KOTA BERKELANJUTAN - Nugroho, Agung Cahyo (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2009)
Kampong is one of the human settlement in urban area that can be describe as traditional housingbefore the modern planning of settlement attached to cities in Indonesia. Kampong as the embryois the root of growth for Indonesian cities, so that the urban planning must give more attention tothis type as planning basic. Kampong is the resource of civilization, creativity and culture forurban areas because of its conditions and limitations. The Localities inside will give the characterfor new spirit of urbanism that fit with local condition, base on sustainable urban settlementideology. By digging the social, economic, culture and character of settling in kampong, this canbe platform for the forming of new paradigm in Indonesia urban settlement planning anddesigning, to make the better quality of urban space. This goals can be reach with some basicprinciples for urban planning base on the existence of urban kampong